Water Diffusivity Changes Along the Perivascular Space After Lumboperitoneal Shunt Surgery in Idiopathic Normal Pressure Hydrocephalus - Kikuta, Junko; Kamagata, Koji; Taoka, Toshiaki; Takabayashi, Kaito; Uchida, Wataru; Saito, Yuya; Andica, Christina; Wada, Akihiko; Kawamura, Kaito; Akiba, Chihiro; Nakajima, Madoka; Miyajima, Masakazu; et al. (Frontiers in Neurology, 2022)
Background The aim of this study was to evaluate the water diffusivity changes along the perivascular space after lumboperitoneal shunt (LPS) surgery in idiopathic normal pressure hydrocephalus. Methods Nine patients diagnosed with idiopathic normal pressure hydrocephalus (iNPH; three men and six women, mean age ± SD = 75.22 ± 5.12 years) according to the guidelines for iNPH in Japan were included in the study. Post-LPS surgery, six patients with iNPH who exhibited improvement in symptoms were defined as responder subjects, while three patients with iNPH who did not were defined as non-responder subjects. We calculated the mean analysis along the perivascular space (ALPS) index of the left and right hemispheres and compared the differences between pre- and post-LPS surgery mean ALPS indices in iNPH patients. In the responder or non-responder subjects, the mean ALPS indices in the pre- and post-operative iNPH groups were compared using Wilcoxon signed-rank tests. Next, correlation analyses between pre- and post-operation changes in the mean ALPS index and clinical characteristics were conducted. Results The mean ALPS index of the post-operative iNPH group was significantly higher than that of the pre-operative iNPH group (p = 0.021). In responder subjects, the mean ALPS index of the post-operative iNPH group was significantly higher than that of the pre-operative iNPH group (p = 0.046). On the other hand, in the non-responder subjects, the mean ALPS index of the post-operative iNPH group was not significantly different compared to the pre-operative iNPH group (p = 0.285). The mean ALPS index change was not significantly correlated with changes in the Mini-Mental State Examination (MMSE) score (r = −0.218, p = 0.574), Frontal Assessment Battery (FAB) score (r = 0.185, p = 0.634), Trail Making Test A (TMTA) score (r = 0.250, p = 0.516), and Evans' index (r = 0.109, p = 0.780). In responder subjects, the mean ALPS index change was significantly correlated with Evans' index in pre-operative patients with iNPH (r = 0.841, p = 0.036). Conclusion This study demonstrates the improved water diffusivity along perivascular space in patients with iNPH after LPS surgery. This could be indicative of glymphatic function recovery following LPS surgery.